Pharmacokinetics and hepatoprotective effects of Lippia scaberrima Sond. and Aspalathus linearis (Burm.f.) R. Dahlgren - Lall, Namrita (University of Pretoria, 2024)
Thesis (PhD (Medicinal Plant Sciences))--University of Pretoria, 2020.